Production management model to reduce late deliveries in a metal-mechanical SME using lean tools - Orellana-Nuñez, Nicole (2022)
The metal-mechanic industry is indispensable for the economic growth of a country since it generates capital goods for industrial sectors at a national and international level. Currently, metal-mechanic SMEs face different challenges to meet their customers' demand at the right time and with quality products. The article studies a medium-sized metal-mechanic company with an on-time delivery percentage of 66.94%, generating dissatisfaction in its customers and economic losses close to 50 thousand dollars. To solve the problem, a production management model is proposed exclusively for SMEs with MTO production systems that includes 4 Lean tools. To validate the model, a pilot program was chosen, and an adequate production rate was achieved to meet the required production demand, thus validating the efficiency of lean techniques to solve problems in a scenario of medium-sized manufacturing companies.